Automated analysis of spoken language differentiates multiple system atrophy from Parkinson's disease - Šubert, Martin; Tykalová, Tereza; Novotný, Michal; Dušek, Petr; Klempíř, Jiří; Rusz, Jan (Journal of neurology, 2025)
BACKGROUND AND OBJECTIVES: Patients with synucleinopathies such as multiple system atrophy (MSA) and Parkinson's disease (PD) frequently display speech and language abnormalities. We explore the diagnostic potential of automated linguistic analysis of natural spontaneous speech to differentiate MSA and PD. METHODS: Spontaneous speech of 39 participants with MSA compared to 39 drug-naive PD and 39 healthy controls matched for age and sex was transcribed and linguistically annotated using automatic speech recognition and natural language processing. A quantitative analysis was performed using 6 lexical and syntactic and 2 acoustic features. Results were compared with human-controlled analysis to assess the robustness of the approach. Diagnostic accuracy was evaluated using sensitivity analysis. RESULTS: Despite similar disease duration, linguistic abnormalities were generally more severe in MSA than in PD, leading to high diagnostic accuracy with an area under the curve of 0.81. Compared to controls, MSA showed decreased grammatical component usage, more repetitive phrases, shorter sentences, reduced sentence development, slower articulation rate, and increased duration of pauses, whereas PD had only shorter sentences, reduced sentence development, and longer pauses. Only slower articulation rate was distinctive for MSA while unchanged for PD relative to controls. The highest correlation was found between bulbar/pseudobulbar clinical score and sentence length (r = -0.49, p = 0.002). Despite the relatively high severity of dysarthria in MSA, a strong agreement between manually and automatically computed results was achieved. DISCUSSION: Automated linguistic analysis may offer an objective, cost-effective, and widely applicable biomarker to differentiate synucleinopathies with similar clinical manifestations.
Keywords: Natural language processing; Multiple System Atrophy; Male; Spontaneous discourse; Automated linguistic analysis; Multiple system atrophy; multisystémová atrofie; Diagnosis, Differential; Aged; mužské pohlaví; senioři; Natural Language Processing; lidé; ženské pohlaví; Humans; zpracování přirozeného jazyka; diferenciální diagnóza; Language; Female; Parkinson Disease; Parkinsonova nemoc; lidé středního věku; Middle Aged